2022
DOI: 10.1126/sciadv.abg8335
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-induced loss of beneficial gut bacterial extracellular vesicles is associated with the pathogenesis of osteonecrosis

Abstract: Osteonecrosis of the femoral head (ONFH) commonly occurs after glucocorticoid (GC) therapy. The gut microbiota (GM) participates in regulating host health, and its composition can be altered by GC. Here, this study demonstrates that cohousing with healthy mice or colonization with GM from normal mice attenuates GC-induced ONFH. 16 S rRNA gene sequencing shows that cohousing with healthy mice rescues the GC-induced reduction of gut Lactobacillus animalis . Oral su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 57 publications
0
51
0
Order By: Relevance
“…Among the 60 of them, 15 and 45 concerned Gram-negative and Gram-positive bacteria, respectively. All articles assessed the size of the produced EVs, of which 49 determined it using only one technique (21 with electron microscopy [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], 19 with NTA [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ], and 9 with DLS [ 42 , 45 , 49 , 50 , 91 , 92 ,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 60 of them, 15 and 45 concerned Gram-negative and Gram-positive bacteria, respectively. All articles assessed the size of the produced EVs, of which 49 determined it using only one technique (21 with electron microscopy [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], 19 with NTA [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ], and 9 with DLS [ 42 , 45 , 49 , 50 , 91 , 92 ,…”
Section: Discussionmentioning
confidence: 99%
“…Only 9 papers analyzed the electrical charge of EVs, of which 7 used DLS [ 31 , 36 , 37 , 38 , 39 , 42 , 45 ] and 2 used NTA [ 84 , 85 ]. The quantity of EVs produced was examined in 18 articles, of which 14 used NTA [ 31 , 33 , 38 , 39 , 72 , 73 , 74 , 76 , 77 , 79 , 83 , 87 , 88 , 89 ], 2 used TRSP [ 49 , 50 ], 1 used flow cytometry [ 45 ], and 1 used spectrophotometry [ 51 ]. Detailed information on the numerical data of the above-presented results can be found in Table S1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al recently demonstrated the osteoprotective effects of specific enterobacteria and their extracellular vesicles in a study (EVs) [ 66 ]. Glucocorticoid (GC)-induced osteonecrosis of the femoral head (ONFH) mice caged with healthy mice alleviated ONFH symptoms and restored the GC-induced reduction of intestinal bacteria L. animalis and extracellular vesicles from L. animalis ( L. animalis -EVs).…”
Section: Recent Pre-clinical and Clinical Postbiotic Studiesmentioning
confidence: 99%
“…Glucocorticoid-induced loss of beneficial gut bacterial extracellular vesicles is associated with the pathogenesis of osteonecrosis. Beneficial gut bacterial extracellular vesicles can enter the femoral head, increase angiogenesis and bone formation, reduce apoptosis, and alleviate bone destruction symptoms ( 19 ). Jones et al.…”
Section: Introductionmentioning
confidence: 99%